Boron Fullerene B80 Doped with Hydrogen and Phosphorus Atoms - Ganji, M.D.; Hesami, M.; Nourozi, F.; Ghobakhlou, M. (Asian Journal of Chemistry, 2011)
The incorporated H and P atoms in B80 fullerene, is examined within the first-principles density functional theory (DFT) calculations for possible applications as single quantum bits (qubits) in solid-state quantum computers as well as molecular electronics devices. It was observed atomic displacement of both H and P atoms from the center of the cage so that the wall B atoms can form covalent bonds with encapsulated atoms making them unavailable for hyperfine contact coupling to the nuclear spin. Hence, B80 fullerene nanocage may not be suitable for the solidstate quantum computers. However, the electronic structure for incorporated nanocages is significantly modified by the reduction of the band gap, inducing a metallic character to the encapsulated fullerene. This open the way towards the assessing the possibility to create molecular electronic nano-devices.